Operation and control of multi-area multi-microgrid systems - John, Thomas (2017)
There has been a widespread deployment of microgrids around the world in recent years. Microgrids form a local area power distribution system with distributed generations, energy storage systems and controllable loads. The next stage of innovation in the field of microgrid systems is the interconnection of several AC and DC microgrid systems spread over large geographical distances to form multi-area multi-microgrid (MMG) systems, which will satisfy the ever increasing global energy demands. There are several benefits associated with these MMG systems such as improved reliability and security of power supply, mutual power sharing and reduced investment in new generating capacity. For the effective operation and control of these MMG systems during different modes of operation, effective methods of power, voltage and frequency controls are essential.